2022
DOI: 10.2196/28638
|View full text |Cite
|
Sign up to set email alerts
|

Engagement With a Mobile Phone–Based Life Skills Intervention for Adolescents and Its Association With Participant Characteristics and Outcomes: Tree-Based Analysis

Abstract: Background Mobile phone–delivered life skills programs are an emerging and promising way to promote mental health and prevent substance use among adolescents, but little is known about how adolescents actually use them. Objective The aim of this study is to determine engagement with a mobile phone–based life skills program and its different components, as well as the associations of engagement with adolescent characteristics and intended substance use a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…With regard to program use, the results of this study are in line with previous studies that found higher use among younger youth and those without a migration background [16,17,21]. Within this study, which was conducted exclusively in the Germanspeaking part of Switzerland, it was also shown, however, that the origin of the young person or a parent from a non-German-speaking country of origin was the best predictor of low program use.…”
Section: Principal Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…With regard to program use, the results of this study are in line with previous studies that found higher use among younger youth and those without a migration background [16,17,21]. Within this study, which was conducted exclusively in the Germanspeaking part of Switzerland, it was also shown, however, that the origin of the young person or a parent from a non-German-speaking country of origin was the best predictor of low program use.…”
Section: Principal Resultssupporting
confidence: 90%
“…Of these, 1473 (83.7%) students with a mean age of 15.4 years participated in the program and the respective study. Adolescents who did not drink in a problematic way and had better educational levels were the ones who used the program the most; on average, program participants reacted to half of the prompted activities [21].…”
Section: Introductionmentioning
confidence: 99%
“…Details on the theoretical and technologic background of the program and its contents are provided elsewhere. 27,31 The interventional elements of the program were based on social cognitive theory. 20,21 Individually tailored web-based feedback was provided to study participants in the intervention group immediately after they completed the baseline online assessment within their school classroom.…”
Section: Interventionmentioning
confidence: 99%
“…A second benefit of health text messages is their relatively low cost in implementation and the delivery of content uniformly across a population [ 7 ]. Several text message interventions have been developed for adolescents, aiming to improve a variety of health outcomes, such as weight management [ 8 ], physical activity [ 9 ], mental health [ 10 ], diabetes outcomes [ 11 ], and social well-being [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%